2008
DOI: 10.1017/s174392130902924x
|View full text |Cite
|
Sign up to set email alerts
|

The mid-term periodicities in sunspot areas

Abstract: Abstract. The sunspot area fluctuations for the northern and the southern hemispheres of the Sun over the epoch of 12 cycles (12-23) are investigated. Because of the asymmetry of their probability distributions, the positive and the negative fluctuations are considered separately. The auto-correlation analysis of them shows three quasi-periodicities at 10, 17 and 23 solar rotations. The wavelets gives the 10-rotation quasi-periodicity. For the original and the negative fluctuations the correlation coefficient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Prabhakaran Nayar et al (2002) showed a significant wavelet power of the daily Wolf numbers at periods around 11 -12 rotations for short time-intervals during several solar maxima. The auto-correlation and the wavelet analyses of rotational data for each solar hemisphere confirmed the dominance of this periodicity (Getko, 2009). …”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Prabhakaran Nayar et al (2002) showed a significant wavelet power of the daily Wolf numbers at periods around 11 -12 rotations for short time-intervals during several solar maxima. The auto-correlation and the wavelet analyses of rotational data for each solar hemisphere confirmed the dominance of this periodicity (Getko, 2009). …”
Section: Discussionmentioning
confidence: 59%
“…To verify the stationarity conditions of {X (Getko, 2009), the positive and negative fluctuations were considered separately. For {F n i } they can be defined as follows:…”
Section: The Stationary Version Of Sunspot Area Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations